Lack of communication between healthcare professionals and women with ovarian cancer about sexual issues - Stead, M L (Nature Publishing Group, 2003)
Gynaecological cancer has been shown to affect women's sexual functioning, yet evidence suggests that healthcare professionals rarely discuss sexual issues with women diagnosed with a gynaecological cancer. Few studies have investigated why there is a lack of communication between healthcare professionals and women about sexual issues. Our study investigated the attitudes and behaviours of the 27 doctors and 16 nurses treating women with ovarian cancer in our centre towards the discussion of sexual issues, and also investigated women's experiences of such communication. Our findings showed that although most healthcare professionals thought that the majority of women with ovarian cancer would experience a sexual problem, only a quarter of doctors and a fifth of nurses actually discussed sexual issues with the women. Reasons for not discussing sexual issues included ‘it is not my responsibility’, ‘embarrassment’, ‘lack of knowledge and experience’ and ‘lack of resources to provide support if needed’. While some of these reasons were also viewed as barriers by the women, the results demonstrate that there is a need from the women's perspective to improve communication about sexual issues, although the most appropriate approach to this remains to be investigated.